Advances in Government Policy and Regulatory Communication: Nigeria Customs Service Perspective - Abdullahi Aliyu Maiwada (Polit Journal Scientific Journal of Politics, 2025)
Effective communication is central to the success of government policy implementation and regulatory enforcement, particularly in complex governance systems such as Nigeria. This paper explores the advances in government policy and regulatory communication from the perspective of the Nigeria Customs Service (NCS), a key agency responsible for trade facilitation and revenue generation, suppression of smuggling and implementation of government fiscal policies. Drawing on contemporary scholarly literature and practical case studies, the paper examines how the NCS has increasingly adopted strategic communication tools, such as digital platforms, stakeholder engagement, public awareness campaigns, and media framing, to improve transparency, facilitate compliance, and enhance institutional credibility. It highlights key initiatives, including the implementation of the Pre-Arrival Assessment Report (PAAR), the border closure policy, and the ongoing trade modernisation project, as evidence of the agency’s evolving communication practices. The paper also discusses the challenges that continue to undermine effective regulatory communication, including policy inconsistency, infrastructural constraints, misinformation, and limited professional communication capacity. The paper concludes that while significant progress has been made, sustained improvement in regulatory communication within the NCS requires institutional reforms, enhanced inter-agency coordination, and the professionalisation of communication functions to foster inclusive, accountable, and efficient public governance.